Spike S2 Subunit: Possible Target for Detecting Novel SARS-CoV-2 Variants with Multiple Mutations - Teerada Ponpinit; Yutthana Joyjinda; Weenassarin Ampoot; Siriporn Yomrat; Phatthamon Virojanapirom; Chanida Ruchisrisarod; Abhinbhen W. Saraya; Pasin Hemachudha; Thiravat Hemachudha (Tropical Medicine and Infectious Disease, 2024)
Novel SARS-CoV-2 variants have multiple mutations that may impact molecular diagnostics. The markedly conserved S2 subunit may be utilized to detect new variants. A comparison of 694 specimens (2019–2022) in Thailand using a commercial RT-PCR kit and the kit in combination with S2 primers and a probe was performed. Delayed amplification in ORF1ab was detected in one BA.4 omicron, whereas no amplification problem was encountered in the S2 target. There were no statistically significant differences in mean Ct value between the target genes (E, N, ORF1ab, and S2) and no significant differences in mean Ct value between the reagents. Furthermore, 230,821 nucleotide sequences submitted by 20 representative counties in each region (Jan–Oct 2022) have been checked for mutations in S2 primers and probe using PrimerChecker; there is a very low chance of encountering performance problems. The S2 primers and probe are still bound to the top five currently circulating variants in all countries and Thailand without mismatch recognition (Jun–Nov 2023). This study shows the possible benefits of detecting S2 in combination with simultaneously detecting three genes in a kit without affecting the Ct value of each target. The S2 subunit may be a promising target for the detection of SARS-CoV-2 variants with multiple mutations.